PLGA-Based Nanoplatforms in Drug Delivery for Inhibition and Destruction of Microbial Biofilm - Shariati, Aref; Chegini, Zahra; Ghaznavi-Rad, Ehsanollah; Zare, Ehsan Nazarzadeh; Hosseini, Seyed Mostafa (Frontiers in Cellular and Infection Microbiology, 2022)
The biofilm community of microorganisms has been identified as the dominant mode of microbial growth in nature and a common characteristic of different microorganisms such as Pseudomonas aeruginosa, Staphylococcus aureus, and Staphylococcus epidermidis. The biofilm structure helps in the protection from environmental threats including host immune system and antimicrobial agents. Thus, the biofilm community has led to a higher prevalence of multidrug-resistant (MDR) strains in recent years. In this regard, the use of a new class of antibiotics, natural compounds, and anti-biofilm enzymes has been considered for the destruction of the microbial biofilm. However, different drawbacks such as low penetration, high susceptibility to degradation, instability, and poor solubility in aqueous solutions limit the use of anti-biofilm agents (ABAs) in a clinical setting. As such, recent studies have been using poly lactic-co-glycolic acid (PLGA)-based nanoplatforms (PLGA NPFs) for delivery of ABAs that have reported promising results. These particles, due to proper drug loading and release kinetics, could suppress microbial attachment, colonization, and biofilm formation for a long time. Additionally, PLGA NPFs, because of the high drug-loading efficiencies, hydrophilic surface, negative charge, and electrostatic interaction, lead to effective penetration of antibiotics to the deeper layer of the biofilm, thereby eliminating the microbial biofilm. Thus, PLGA NPFs could be considered as a potential candidate for coating catheters and other medical material surfaces for inhibition and destruction of the microbial biofilm. However, the exact interaction of PLGA NPFs and the microbial biofilm should be evaluated in animal studies. Additionally, a future goal will be to develop PLGA formulations as systems that can be used for the treatment of the MDR microbial biofilm, since the exact interactions of PLGA NPFs and these biofilm structures are not elucidated. In the present review article, we have discussed various aspects of PLGA usage for inhibition and destruction of the microbial biofilm along with different methods and procedures that have been used for improving PLGA NPF efficacy against the microbial biofilm.